Soil mycobiome is shaped by vegetation and microhabitats: A regional-scale study in Southeastern Brazil - Yamauchi, Danielle Hamae [UNESP]; Garces, Hans Garcia [UNESP]; Teixeira, Marcus De Melo; Rodrigues, Gabriel Fellipe Barros [UNESP]; Ullmann, Leila Sabrina [UNESP]; Garces, Adalberto Garcia [UNESP]; Hebeler-Barbosa, Flavia [UNESP]; Bagagli, Eduardo [UNESP] (MDPI, 2021)
Soil is the principal habitat and reservoir of fungi that act on ecological processes vital for life on Earth. Understanding soil fungal community structures and the patterns of species distribution is crucial, considering climatic change and the increasing anthropic impacts affecting nature. We evaluated the soil fungal diversity in southeastern Brazil, in a transitional region that harbors patches of distinct biomes and ecoregions. The samples originated from eight habitats, namely: Semi-deciduous forest, Brazilian savanna, pasture, coffee and sugarcane plantation, abandoned buildings, owls’ and armadillos’ burrows. Forty-four soil samples collected in two periods were evaluated by metagenomic approaches, focusing on the high-throughput DNA sequencing of the ITS2 rDNA region in the Illumina platform. Normalized difference vegetation index (NDVI) was used for vegetation cover analysis. NDVI values showed a linear relationship with both diversity and richness, reinforcing the importance of a healthy vegetation for the establishment of a diverse and complex fungal community. The owls’ burrows presented a peculiar fungal composition, including high rates of Onygenales, commonly associated with keratinous animal wastes, and Trichosporonales, a group of basidiomycetous yeasts. Levels of organic matter and copper influenced all guild communities analyzed, supporting them as important drivers in shaping the fungal communities’ structures.
Keywords: Fungal communities; NDVI; Soil mycobiome